Identity in crossroads civilisations: ethnicity, nationalism and globalism in Asia - Kolig, Erich; Wong, Sam ca. 20./21. Jh.; Angeles, Vivienne S. M. (ICAS publications series. Edited volumes, 2009)
Based on multi-disciplinary studies conducted in Asia (India, Bhutan, China, Japan, Malaysia, Philippines, New Zealand), this volume on Identity in Crossroad Civilisations: Ethnicity, Nationalism and Globalism in Asia demonstrates how identity is defined, negotiated and conceptualised in response to increasing globalisation in the region. Asian expressions of identity reflect, in many ways, their adaptability to the changing economic, political and social climates and at the same time question Samuel Huntington's popular yet controversial thesis on the clash of civilisations. This book also engages Benedict Anderson's idea of 'imagined communities' and shows how its operation impacts on both community and individual identity in an environment that is increasingly characterised by border crossings and transnationalism. Contemporary Asian realities, as examined in the essays, demonstrate the need to rethink previous notions of identity and nationalism